2004
DOI: 10.1097/01.hpc.0000128714.35330.6d
|View full text |Cite
|
Sign up to set email alerts
|

Implications of the Mechanical (PCI) vs Thrombolytic Controversy for ST Segment Elevation Myocardial Infarction on the Organization of Emergency Medical Services

Abstract: With the many advances in rapid reperfusion therapy for management of acute ST segment elevation myocardial infarction (STEMI), there is a need to revisit the current plan for prehospital triage (point of entry). Until recently in Boston, and nationwide, there has been a policy that patients with suspected acute MI were brought to the nearest hospital. Then, if ST segment elevation was present, patients were treated with either thrombolytic therapy or primary percutaneous coronary intervention (PCI). Recent da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
30
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 40 publications
0
30
0
Order By: Relevance
“…Notwithstanding the above concerns, both the Minneapolis Heart Institute and the Mayo Clinic regional STEMI networks, in addition to other ongoing efforts in many states such as the Reperfusion of Acute Myocardial Infarction in Carolina Emergency Departments (RACE) program in North Carolina 12 and the Emergency Medical Services Point of Entry program in Boston, 13 have taught us that establishment of regional systems and centers of care for STEMI patients is possible. These efforts are energized by the knowledge that in many patients (those at high risk, those who present relatively late [Ͼ3 hours] after symptom onset, and those in whom fibrinolysis is contraindicated), primary PCI is the only option.…”
Section: Articles Pp 721 and 729mentioning
confidence: 99%
“…Notwithstanding the above concerns, both the Minneapolis Heart Institute and the Mayo Clinic regional STEMI networks, in addition to other ongoing efforts in many states such as the Reperfusion of Acute Myocardial Infarction in Carolina Emergency Departments (RACE) program in North Carolina 12 and the Emergency Medical Services Point of Entry program in Boston, 13 have taught us that establishment of regional systems and centers of care for STEMI patients is possible. These efforts are energized by the knowledge that in many patients (those at high risk, those who present relatively late [Ͼ3 hours] after symptom onset, and those in whom fibrinolysis is contraindicated), primary PCI is the only option.…”
Section: Articles Pp 721 and 729mentioning
confidence: 99%
“…The first is the "bypass" model in which patients with a diagnosis of STEMI on a prehospital ECG are transported directly to a PCI center, bypassing a closer hospital without PCI capability. 22 The second is the "transfer" model in which interhospital transfer is accomplished rapidly through carefully established treatment protocols using integrated hospital systems. 23 Another option is to establish primary PCI programs without onsite surgery, but it is unclear whether this option really increases access to primary PCI by skilled operators and experienced teams.…”
Section: Primary Pci Strategy Limitations Accessmentioning
confidence: 99%
“…29 Other communities, typically urban in location, have adopted a strategy of direct transportation for all STEMI patients to a dedicated primary PCI center that is available 24 hours a day, 7 days per week. 4 No large-scale randomized trials comparing such reperfusion strategies have been reported to date; however, it is recognized by the writing committee for the ACC/AHA Guidelines for the Management of Patients With STEMI and the AWG that the critical considerations in the delivery of primary PCI are the interrelated issues of timeliness and access. If timely access to primary PCI is available, the evidence suggests that PCI is the preferred reperfusion strategy, especially in those presenting late after symptom onset, those who are considered high risk, and those in whom fibrinolysis is contraindicated.…”
Section: The Time From Onset Of Symptoms Data Exist That Indicatementioning
confidence: 99%
“…In fact, several regions have established both triage and transfer protocols for PCI in patients with STEMI. 4,5 The AHA, which is dedicated to reducing disability and death due to cardiovascular diseases and stroke, has recog-*The opinions expressed in this manuscript are those of the authors and should not be construed as necessarily representing an official position of the Centers for Disease Control and Prevention, the United States Department of Health and Human Services, or the United States Government.The American Heart Association makes every effort to avoid any actual or potential conflicts of interest that may arise as a result of an outside relationship or a personal, professional, or business interest of a member of the writing panel. Specifically, all members of the writing group are required to complete and submit a Disclosure Questionnaire showing all such relationships that might be perceived as real or potential conflicts of interest.…”
mentioning
confidence: 99%
See 1 more Smart Citation